S81 Refractory asthma in the UK: a follow-up analysis. (2nd December 2011) - Sweeney, J; Brightling, C E; Menzies-Gow, A; Niven, R M; Heaney, L G
Abstract : Introduction: Refractory asthma poses a major healthcare problem with limited therapies currently available and new therapies needed. The British Thoracic Society (BTS) Difficult Asthma Network has previously published demographic data on a cohort of patients with well-characterised refractory asthma1 using a National Registry and detailed follow-up data is now available. Methods: Data on 349 of the original 382 patients was available from 4 specialist centres across the UK–Royal Brompton Hospital, London, Glenfield Hospital, Leicester, University Hospital of South Manchester and Belfast City Hospital. Data have been used to examine healthcare utilisation, therapeutic strategies and lung function compared to baseline. Results: The median follow-up period was 3.1 years (IQR 1.9–5.5 years). Improvements from baseline were noted in Pre bronchodilator FEV1 % predicted (66%±23.6% vs 72.7%±26.8%; p<0.001) and Pre bronchodilator FVC% predicted (82.7%±20.3% vs 86.5%±21.5%; p<0.01). Reduced rescue steroids (Median 2IQR 4–6 vs 0 IQR 2–4; p<0.001), a reduction in hospital admissions (Median 0 IQR 0–2 vs 0 IQR 0–1; p<0.01) and reduced unscheduled visits to GP's or A&E (Median 4 IQR 2–6 vs 2 IQR 0–6; p<0.05) was seen. The most frequent therapeutic intervention was the introduction of maintenance oral steroids (OCS): 42% of the original cohort was on maintenance OCS at baseline, with 58% on maintenance OCS at follow-up. Most on OCS at baseline remained on OCS but 30 (9%) discontinued and 78 (22%) had OCS initiated. Steroid sparing agents (methotrexate, cyclosporine, azathioprine etc) were tried but showed minimal steroid sparing benefit with a success rate of between 0.6 and 3.2%. Omalizumab was only suitable for trial in 59 (17%) subjects with a response rate of 66%. In those who had a successful Omalizamub trial, 23 (92%; p<0.001) were successful in achieving either a reduction in OCS or complete withdrawal. Conclusion: In specialist centres, healthcare outcomes and lung function are improved in patients with refractory asthma. The most frequent intervention is the progression to maintenance OCS and treatment options remain limited. Steroid sparing agents show little benefit with the exception of Omalizamub.